DISTRIBUTIONS OF ANTHROPOMETRIC MEASUREMENTS OF NEW BORN BABIES AMONG VARIOUS ETHNIC GROUPS IN MAIDUGURI, NIGERIA: A PROSPECTIVE STUDY - Takai IU; Audu BM; Bukar M; Abudu OO; Geidam AD (Ntec Specialist, 2014)
Background: Weight and other newborn anthropometric measurements at birth are considered as the most important indicators of a newborn's chances of survival, growth, long-term health and psychosocial development. Objective: To determine the mean birth weight, birth length and head circumferences of new born babies among the various ethnic groups in Maiduguri. Method: A descriptive cohort study involving 854 pregnant women with their live singleton babies was carried out in the Departments of Obstetrics and Gynaecology of the University of Maiduguri Teaching Hospital (UMTH) and the State Specialist Hospital (SSH), Maiduguri, over a 6-month period, between 2nd February 2009 and 29th July 2009. Mothers' socio-demographic and obstetrics performances, baby's birth weights, birth lengths and head circumferences were obtained and recorded and data analyzed using SPSS version 16. Statistical significance was computed by t-test and Chi-square. A P value less than 0.05 was considered significant. Results: A total of 854 mothers together with their 854 live singleton babies were studied. There were 460 (53.9%) male and 394 (46.1%) female babies. Among these babies, 144 were low birth weight, 660 had normal birth weight while high birth weight was seen in 50 babies. The mean birth weight of all babies delivered in the study population was 3030.47±631g, with mean birth length of 47.8±3.1cm, and the mean head circumference was 34.2±2. All the parameters studied were significantly lower in those that were of LBW compared to babies that were not of LBW, and the mean difference was statistically significant (P value 0.000). Conclusion: All the anthropometric measurements were highest in Igbo newborns while Hausa/Fulani had the lowest among the various ethnic groups studied in Maiduguri. Improving the socio-economic status especially of the disadvantage ethnic group and further community based research is recommended